Formononetin triggers ferroptosis in triple-negative breast cancer cells by regulating the mTORC1/SREBP1/SCD1 pathway - Xie, Dong; Jiang, Yulang; Wang, Huan; Zhu, Lingyi; Huang, Shuangqin; Liu, Sheng; Zhang, Weihong; Li, Tian (Frontiers in Pharmacology, 2024)
Triple negative breast cancer (TNBC) is the most malignant type of breast cancer, and its prognosis is still the worst. It is necessary to constantly explore the pathogenesis and effective therapeutic targets of TNBC. Formononetin is an active ingredient with anti-tumor effects that we screened earlier. The main purpose of this study is to elucidate mechanism of the inhibitory effect of Formononetin on TNBC. In our study, Formononetin exhibits significant inhibitory effects on the proliferation of triple TNBC, both in vivo and in vitro. Moreover, it elicits an increase in lipid peroxide levels, downregulates the expression of ferroptosis-associated proteins GPX4 and xCT, and induces ferroptosis in breast cancer cells. Concurrently, Formononetin impedes the formation of the mammalian target of rapamycin complex 1(mTORC1) and suppresses the expression of downstream Sterol regulatory element-binding protein 1(SREBP1). The utilization of breast cancer cells with SREBP1 overexpression or knockout demonstrates that Formononetin induces ferroptosis by modulating the mTORC1-SREBP1 signaling axis. In conclusion, this study provides evidence that Formononetin exerts an anti-proliferative effect on triple negative breast cancer by inducing ferroptosis. Moreover, the mTORC1-SREBP1 signal axis is identified as the primary mechanism through which formononetin exerts its therapeutic effects. These findings suggest that formononetin holds promise as a potential targeted drug for clinical treatment of TNBC.